Using AAC Media To Improve Dynamics Ability In Music Learning For Autistic Children - Lalan Erlani; Tati Narawati; Zaenal Alimin (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
This study aims to improve the ability of dynamics musical skills of autistic student using Augmentative and alternative communication (AAC) media. Augmentative and alternative communication (AAC) interventions have been shown to improve both communication and learning skills in children and youth with autism spectrum disorders and other developmental disabilities. There are many strategies educators use to aid a child to communicate. Visual aides have been used successfully in helping children with autism communicate. A picture system called AAC Media allows teachers to make pictures to help students on the spectrum communicate. The method that being used in this study is experimental method with single subject research approach and using the design of A–B pattern. Data collection technique that being used are observation and documentation. And data analysis technique that being used is visual analysis in condition. The results of this research indicate that musical dynamic skills in music subject could be improved by using AAC media. The use of AAC media brings positive impact towards autistic students skills in musical dynamic. Therefore, teachers can apply the using of AAC media on music subject activities in school.